Studi Mikroanatomi Pankreas Kodok Lembu Menggunakan Metode Pewarnaan Baku dan Immunohistokimia (MICROSCOPICAL STUDY OF PANCREAS OF BULLFROG USING CONVENTIONAL AND IMMUNOSTAINING METHODS) - Adnyane, I Ketut Mudite; ., Supratikno; Winarto, Adi; Agungpriyono, Srihadi (Jurnal Veteriner, 2012)
Morphology, distribution and relative frequency of endocrine cells in the pancreas Bullfrog (Ranacatesbeiana) were studied using conventional and immunohistochemical methods. Samples pancreas takenfrom ten adult Bullfrogs (five males and five females). In general, pancreas of the Bullfrog consists ofexocrine portion, endocrine portion (Langerhans islets) and ducts. The Langerhans islets were distributedamong the exocrine portion of pancreas. Endocrine cells in the pancreas of Bullfrog were polimorph, round,oval or triangular in shapes with bipolar cytoplasmic granules. Glucagon cells were distributed mainly inthe peripheral, insulin cells in the center while the somatostatin cells in the area between glucagon andinsulin cells of Langerhans islet. The number of the glucagon cells were higher compare to the number ofinsulin and somatostatin cells.
Keywords: Bullfrog, pancreas, immunohistochemistry